Inorganic material thick film and method for forming same

An all-inorganic thick film using polysiloxane and metal oxide compounds addresses the challenges of aging infrastructure and radioactive waste management by providing long-lasting protection and reducing maintenance costs, with applications in infrastructure repair and waste containment.

JP7606181B2Active Publication Date: 2024-12-25NATIONAL INSTITUTE OF ADVANCED INDUSTRIAL SCIENCE & TECHNOLOGY +1
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
JP2024503700
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-10-28
Filing Date
2023-10-27
Publication Date
2024-12-25
Estimated Expiration
2043-10-27

AI Technical Summary

Technical Problem

Aging infrastructure and radioactive waste management pose significant challenges due to high maintenance and management costs, with conventional paints and coatings failing to provide long-term protection against corrosion and deterioration, especially in harsh environments.

Method used

Development of an all-inorganic thick film composed of metals or metal oxides, formed using a hybrid composition that includes polysiloxane compounds, silicon-containing compounds, organometallic compounds, and fused silica, which can be applied at low temperatures without organic binders, providing a semi-permanent protective coating.

Benefits of technology

The all-inorganic thick film extends the lifespan of infrastructure and waste containers, reducing maintenance costs and enhancing durability against corrosion, UV exposure, and environmental degradation, while also offering additional functionalities such as electromagnetic shielding and luminescence.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007606181000019
    Figure 0007606181000019
  • Figure 0007606181000020
    Figure 0007606181000020
  • Figure 0007606181000021
    Figure 0007606181000021
Patent Text Reader

Abstract

The present invention provides a composition for forming, on a variety of materials, a "thick film" that is "all inorganic", being composed of only metal or metal oxide (ceramic) inorganic materials, and is several µm to several mm thick, or in other words, an "all inorganic thick film". More specifically, by using the present invention, an inorganic thick film that includes substantially no organic substances is formed by applying ultraviolet radiation or heat at a temperature of at most 200°C to a vehicle composition that mainly comprises a plurality of polysiloxane compounds having different molecular weights, or to a composition prepared by adding a function-imparting solid substance to the vehicle composition.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a thick film made of an inorganic material mainly composed of a metal or a metal oxide, and a method for forming the same. TECHNICAL FIELD The present invention relates to a thick film made of an inorganic material mainly composed of a metal or a metal oxide, and a method for forming the same. [Background technology]

[0002] Currently, the "aging infrastructure problem" has become a major social issue. In Japan, during the period of high economic growth from 1955 to 1972, many infrastructures that support our lives were constructed, including roads, tunnels, bridges, water supply and sewerage systems, power lines, dams, port facilities, railways, parks, and hospitals. Fifty years have passed since then, and these infrastructures are aging one after another due to environmental influences in addition to the passage of time. In the next 10 years (2023-2033), the proportion of infrastructure facilities (road bridges, river management facilities (water gates, etc.), port wharves, etc.) that have been in operation for more than 50 years will exceed 50% (tunnels will account for 42%). In addition to abnormal weather on a global scale (large typhoons and heavy rains caused by linear precipitation bands), Japan is a disaster-prone country with earthquakes and volcanoes, and the negative impact of aging infrastructure on daily life and safety is beginning to be felt at an accelerating rate (Figure 1a). The problem of aging infrastructure first came to societal attention when the ceiling collapsed in the Sasago Tunnel on the Chuo Expressway in December 2012 (Figure 1b). This Sasago Tunnel accident brought the issue of aging infrastructure into the spotlight as a threat to the safety of people's lives. The Ministry of Land, Infrastructure, Transport and Tourism estimates that infrastructure maintenance and renewal costs will be approximately 195 trillion yen over the 30 years from 2019 to 2048, or around 6 trillion yen per year. However, the national budget for infrastructure repairs is decreasing, and financially struggling local governments are currently unable to respond adequately due to the aging of skilled infrastructure management workers, a shortage of skilled workers, a shortage of personnel, and a lack of financial resources. In this context, the collapse of the Suidobashi Bridge over the Kino River in Wakayama City in October 2021 is still fresh in our memory (Figure 1c). The causes of the collapse were said to be bird droppings, salt damage, and delayed repainting. In the current situation where it is not possible to allocate sufficient budgets for aging infrastructure, what is needed is measures to further reduce maintenance costs. Particularly useful in reducing maintenance costs is the development of paint that can reduce the cost of repainting and the number of times paint needs to be renewed. Reducing the cost of repainting and the number of times paint needs to be renewed for steel structures such as marine civil engineering (bridges in ports and straits) and highways will likely result in budget savings of tens of trillions of yen at the national budget level in the future.

[0003] Even more serious is the deterioration of drums that contain nuclear waste. Radioactive waste generated at facilities that handle nuclear fuel materials is stored or preserved within the facility after undergoing prescribed treatment depending on the type. In order to prevent leakage of radioactive materials due to deterioration of drums over time, regular visual inspections are conducted to check the storage conditions, and if deterioration progresses, the drums are repaired with filament tape and stored in box containers or replaced with new ones. However, the number of drums stored is increasing year by year, and more efficient measures against deterioration over time are required (Figure 1d). In addition, the accident at the Fukushima Daiichi Nuclear Power Plant of Tokyo Electric Power Company that occurred in 2011 has generated not only solid radioactive waste such as debris, but also about 170 tons of contaminated water per day. The contaminated water is treated with an advanced radioactive waste removal system (ALPS) to remove radioactive nuclides other than tritium. This treated water has no effect on the human body, and it has been decided to release it into the ocean, but there are many people who oppose this, and even if all goes well, the treated water will continue to be stored in huge tanks for several decades until the release is completed. To safely manage such facilities, a technology is required to easily and reliably strengthen and repair the containers, and painting technology is also useful for such strengthening and repair.

[0004] Therefore, a paint revolution is needed that will break the stereotype that there is no innovation in paint, and collaboration between the government and private companies to develop innovative paints that extend their service life will be a "social benefit." [Prior art documents] [Non-patent literature]

[0005] [Non-Patent Document 1] Toshio Fukushima, Material Life, 6[3]146~157 [Non-Patent Document 2] Shigeo Hamaguchi,NEW GLASS,Vol.30,No.115 2015 [Non-Patent Document 3] Kyoko Yamahana, West Asian Archaeology, No. 18, 2017, pp. 79-88 [Non-Patent Document 4] S. Music et al., Brazilian Journal of Chemical Engineering Vol.28, No.01, pp.89-94 Summary of the Invention [Problem to be solved by the invention]

[0006] In response to various problems related to aging infrastructure and waste generated from facilities that handle radioactive materials, the inventors have devoted themselves to developing a technology for forming thick films made entirely of inorganic materials that can improve or restore the strength of materials by coating not only rusted steel and deteriorated concrete surfaces, but also the surfaces of various other materials, as a maintenance technology that can reduce maintenance costs.

[0007] Even if metal structures and buildings are thoroughly painted, they will rust, corrode, and become brittle when exposed to ultraviolet rays, wind, rain, and sea air (for example, Figure 1a).

[0008] To maintain corroded steel like this, the old paint is removed from the surface of the steel, and rust, salt, moisture, dust, and other deposits are removed from the corroded surface. This type of surface purification work is called "keren." After that, paint is applied to complete the maintenance.

[0009] Stenshell (registered trademark) manufactured by Toyo Aluminum Co., Ltd. is a highly durable rust-resistant metal paint that uses stainless steel flake metal powder as the main ingredient and contains epoxy-based binder resin and urethane-based binder resin, etc., and is a paint with a proven track record of over 30 years (30-year paint). Because it contains metal powder, the unit price is about three times higher than conventional paints, and it has not been used in fields that consume large amounts of paint, such as marine civil engineering and port facilities. However, as an example of steel conservation in 2016 by replacing conventional epoxy and urethane paints with Stenshell (registered trademark), we will explain the repainting of the penstock at the Fujikawa No. 2 Power Plant, which is located on the coast. The penstock has a surface area of ​​3,723.3 m 2 Previously, a three-layer coating of 60μm-thick epoxy resin, 30μm-thick epoxy resin, and 35μm-thick urethane resin was applied every six years. In 2016, a three-layer coating of 70μm-thick epoxy resin primer, 30μm-thick Stenshell (registered trademark) epoxy resin-based intermediate coating (manufactured by Toyo Aluminum Co., Ltd.), and 30μm-thick Stenshell (registered trademark) acrylic urethane resin-based top coating (manufactured by Toyo Aluminum Co., Ltd.) was applied, and as of October 2022, the sixth year after the previous repainting period, the coating film is in good condition, and no corrosion or deterioration is visible in the penstock itself (Figure 2).

[0010] Next, we simulated the maintenance cost for a penstock every 6 years using a conventional resin-based paint that does not contain stainless steel metal powder, and the maintenance cost every 15 years, which is half of the proven 30-year period, using Stenshell (registered trademark) paint that contains high-end stainless steel flake materials (Figure 3a). In addition to the cost of paint, the maintenance work includes the cost of coating design, the cost of assembling and dismantling scaffolding, the cost of scraping, and the cost of coating. In this simulation, the area is 900m 2It was set at 1.6 million yen per maintenance session when using conventional paint, and when using Stenshell (registered trademark) paint, the paint cost is about three times that of conventional paint, but the initial cost is about 1.1 times higher, costing 12.8 million yen. Focusing on the life cycle cost over 30 years, when using conventional paint that requires maintenance every six years, five maintenance tasks are required, and the total cost is calculated to be 58 million yen. On the other hand, when using Stenshell (registered trademark) paint that requires maintenance every 15 years, only two maintenance tasks are required, and the total cost is calculated to be 25.6 million yen. In other words, it was found that by using Stenshell (registered trademark) paint, a life cycle cost (LCC) reduction of 32.4 million yen (-56%) can be achieved over 30 years. The required costs of a general LCC cost chart are "rounded" by item to create a cost index (Figure 3b). It is clear that Stenshell® paint, which uses high-end stainless steel flake raw materials, can lead to significant reductions in 30-year LCC costs.

[0011] The general corrosion process is shown using steel, which is particularly susceptible to rust, as an example (Figure 4, left). A dense passive film of about 3 nm thickness is formed on the surface of steel, but when water comes into contact with the steel surface, anodes and cathodes are generated locally on the steel surface, even on the same metal surface, depending on the material properties and the surrounding environment. A potential difference is generated between the anode and cathode (cell action), and electrons move through the steel, transferring from the anode site to Fe 2+ The iron dissolves in the water, reacts with water to become iron hydroxide, and finally turns into red rust, causing corrosion of the steel. Corrosion progresses especially in the presence of salt or acid. On the other hand, coatings made with Stenshel (registered trademark) are tough because fine stainless steel flakes are layered in the hardened resin, and they are highly resistant to ultraviolet light, external forces, seawater, acids, alkalis, etc., reinforcing the surface of the steel. Also, because of the layered structure of the stainless steel flakes, even if stainless steel flakes are present on the surface of the coating, they do not form local circuits, unlike bulk steel, and because the effective volume of the stainless steel flakes in contact with the steel surface is very small, they do not accept electrons, and as a result, rust does not form on the steel (Figure 4, right).

[0012] Paints for steel structures in marine civil engineering (bridges in ports and straits) and concrete spalling prevention paints leave resins such as epoxy, urethane, and Teflon in the coating. Resins deteriorate and decompose in the environment, and even anti-rust paints have a limited service life.

[0013] Therefore, the inventors of the present invention have investigated a coating made only of inorganic materials, thinking that a thick film made of substantially only inorganic materials such as metals or metal oxides (ceramics) (sometimes referred to as "all-inorganic" in this specification) would further extend the service life of the coating, by eliminating the environmentally degrading resin from Stenshell (registered trademark), which forms a coating that is very useful for solving the problem of aging infrastructure. In the present invention, "consisting essentially of inorganic materials such as metals or metal oxides (ceramics)" means that the amount of organic matter (carbon element) present in the material is less than 2000 ppm, which is the detection limit of energy dispersive X-ray analysis using a scanning electron microscope.

[0014] Examples of coating materials made only of inorganic materials that can be applied to various materials include water glass (Non-Patent Document 1) and glass produced by the sol-gel method (Non-Patent Document 2). However, the thickness of the coating film that can be formed using these materials is about 0.1 to 3 μm. Even if a film is formed to a thickness greater than this, cracks easily occur and the material is not useful as a reinforcing material. However, glassy glazes that cover the surfaces of ceramics and enamel can be seen as far back as ancient Egyptian faience ware, dating back more than 4,000 years (Non-Patent Document 3), and the durability of all-inorganic coatings has been proven.

[0015] Film-forming techniques for forming all-inorganic coatings mainly made of metal or metal oxide (ceramic) include sputtering, electron beam deposition, and chemical vapor deposition, which can produce thin films with a thickness of about 10 nm. In addition, the metal-organic chemical decomposition (MOD) method is a method in which a solution containing a metal-organic compound is applied to form a liquid film, which is then dried and fired. The metal-organic compound is decomposed into metal and organic compounds by heat (thermal decomposition) or excimer laser light (photolysis) that does not generate heat, and the metal or metal oxide (ceramic) is bonded to itself and to the substrate at the same time, forming a thin film of metal oxide with a thickness of about 100 to 200 nm. Furthermore, by using functional inorganic fine particles or a hybrid solution consisting of a metal and a metal-organic compound as a precursor, a thick film of several μm to several tens of μm can be obtained.

[0016] In order to realize innovative components and devices such as electric mobility (automobiles, aircraft) that does not use fossil fuels and ultra-lightweight flexible solar cell modules, composite technology is required to form inorganic material coatings of metal oxides (ceramics) with diverse functions (electricity, light, high temperature resistance, etc.) on substrates of materials such as ceramic material substrates, silicon substrates, and various metal substrates. Conventional inorganic material coating formation requires high-temperature treatment of 500°C or higher (up to 1,500°C), so it could only be applied to heat-resistant materials such as ceramic substrates. Therefore, the National Institute of Advanced Industrial Science and Technology (AIST) developed the optical MOD method, which enables low-temperature coating directly onto a resin substrate through a low-temperature synthesis process using an excimer laser. The ultraviolet light emitted by an excimer laser has a short wavelength and does not generate heat, unlike infrared lasers such as CO2 lasers, making low-temperature processing possible. In this way, optical MOD has greatly expanded the range of substrates on which inorganic material films can be formed. However, the use of an excimer laser places limitations on the objects to which inorganic material films can be formed, and it is not possible to increase the film thickness to the order of millimeters.

[0017] In the conventional film formation techniques described above, in order to form a coating consisting only of inorganic materials such as metal or metal oxide (ceramic), a process under vacuum conditions or a high-temperature treatment process is required, which limits the objects to which the coating can be formed. Furthermore, it is not possible to form a coating with a thickness on the order of millimeters, i.e., a thick film.

[0018] By using paint containing inorganic substances such as metal flakes and organic substances such as resin and solvent, it is possible to obtain a thick coating film with a thickness of several hundred μm to several mm. Such a coating film has a structure in which inorganic substances are dispersed in a hardened resin. Furthermore, by using a thick film paste for electronic materials, it is possible to form a thick film of several μm to several tens of μm made of only inorganic materials. The thick film paste is obtained by kneading inorganic materials such as metals or metal oxides (ceramics) with a solvent and a resin component (binder), and the viscosity characteristics (thixotropy) are controlled by the binder, so that when it is applied to a substrate, a pattern of the desired height can be formed. In the first stage, the formed pattern is heated to about 2 to 300°C in a binder removal process to remove most of the solvent and resin, forming a dried film, and in the second stage, the dried film is fired at a high temperature of about 600 to 1500°C to form a sintered body of metal or metal oxide particles.

[0019] Therefore, the inventors set out to develop a composition (100-year paint) for forming an "all-inorganic thick film" on various materials that is easy to use like conventional paints (curing at room temperature to 200°C), does not require expensive equipment such as an excimer laser, has a service life of 100 years, is "all-inorganic" and is composed only of inorganic materials such as metals or metal oxides (ceramics), and is several μm to several mm thick, that is, a "thick film" by combining the 30-year paint Stenshell (registered trademark) and the light MOD developed by the National Institute of Advanced Industrial Science and Technology. The concept of the technical area targeted by this invention is shown in Figure 5. [Means for solving the problem]

[0020] The present invention provides a vehicle composition capable of forming an all-inorganic coating film mainly composed of a polysiloxane compound, a composition for forming an inorganic thick film containing a function-imparting solid substance in the vehicle, an inorganic thick film of the composition, and a method for forming the same. More specifically, the invention is as follows.

[0021] [1] At least the following ingredients, each as solids: (A) 2 to 98% by weight of a polysiloxane compound, the polysiloxane compound having the general formula (1): [ka] (In the formula, R1 and R2 are each independently a hydrogen atom, 1~3 Alkyl group or C 1~3 m1 and n1 are each independently an integer of 1 to 100, and m1+n1=10 to 100. Both ends of the main chain are independently a hydrogen atom or a C 1~3 A silicone resin represented by the general formula (2): [ka] (In the formula, p is an integer of 250 to 400. Both ends of the main chain are independently a hydrogen atom or a C 1~3 A silicone resin polydimethylsiloxane represented by the general formula (3): [ka] (In the formula, R3 and R4 are each independently a hydrogen atom, 1~3 Alkyl group or C 1~3 m2 and n2 are each independently an integer of 1 to 10, and m2+n2=1 to 10. Both ends of the main chain are independently a hydrogen atom or a C 1~3 or a combination thereof; (B) 0.2 to 20 wt. % of a silicon-containing compound, the silicon-containing compound being selected from tetraalkylorthosilicate (also called "tetraalkoxysilane"; TEOS), silica, a mixture of TEOS and silica, vinyltrimethylsilane, or a combination thereof; (C) 0.5 to 15 weight percent of an organometallic compound, the organometallic compound being titanium diisopropoxybis(ethylacetoacetate), tetrakis(2-ethylhexyl)orthotitanate, or a combination thereof; and (D) 0.5 to 15% by weight of fused silica; and (E) Hardener or UV-curable binder A vehicle composition comprising: [2] As solids, 15 to 70% by weight, preferably 15 to 20% by weight, of a polysiloxane compound, the polysiloxane compound being a silicone resin represented by general formula (1), 2 to 8% by weight of a polysiloxane compound, the polysiloxane compound being a silicone resin represented by general formula (2), and 20 to 85% by weight, preferably 70 to 80% by weight, of a polysiloxane compound, the polysiloxane compound being a silicone resin represented by general formula (3); 0.5 to 3 weight percent titanium diisopropoxybis(ethylacetoacetate); and 0.5 to 3% by weight fused silica and further comprising, as a solid content, based on 100% by weight of the solid content of the above components: Contains 1 to 5% by weight, preferably 2 to 3% by weight, of zirconium octylate; Item 1. The vehicle composition according to item 1. [3] As solids, 45 to 85% by weight, preferably 70 to 85% by weight, of a polysiloxane compound, the polysiloxane compound being a silicone resin represented by general formula (1) and 7 to 24% by weight, preferably 8 to 15% by weight, of a polysiloxane compound, which is a silicone resin represented by general formula (2); And 2-7 wt. %, preferably 2-5 wt. % of the TES reagent Si41 and 0.2-1.5 wt. %, preferably 0.2-0.5 wt. % of the TEOS reagent Si28 and Item 2. The vehicle composition according to item 1, further comprising 0.3 to 3 wt %, preferably 0.3 to 1.5 wt %, of water and 0.3 to 3 wt %, preferably 0.3 to 1.5 wt %, of acetic acid, and further comprising 1 to 5 wt %, preferably 2 to 3 wt %, of zirconium octylate, based on 100 wt % of the solid content of the above components. [4] As solids, 30 to 82% by weight, preferably 30 to 40% by weight, of a polysiloxane compound, which is a silicone resin represented by general formula (2); 3 to 15% by weight, preferably 5 to 12% by weight, of vinyltrimethoxysilane; and 5 to 60% by weight, preferably 50 to 60% by weight, of zirconium octylate Item 2. The vehicle composition according to item 1, comprising: [5] As solids, 9 to 89% by weight, preferably 40 to 50% by weight, of a polysiloxane compound, the polysiloxane compound being a silicone resin represented by general formula (1); 1 to 10% by weight, preferably 5 to 10% by weight, of a silane coupling agent; and 3 to 90% by weight, preferably 40 to 50% by weight, of zirconium octylate Item 2. The vehicle composition according to item 1, comprising: [6] As solids, 97 to 99% by weight of polydimethylsiloxane; and 0.4 to 3.5% by weight, preferably 1 to 2% by weight, of tetrakis(2-ethylhexyl) orthotitanate Item 2. The vehicle composition according to item 1, further comprising 1 to 5% by weight, preferably 2 to 3% by weight, of zirconium octylate as a solid content relative to 100% by weight of the solid content of the above components. [7] As solids, 30 to 98% by weight, preferably 90 to 95% by weight, of a silicone resin which is a polysiloxane compound represented by general formula (2); 0.5 to 6% by weight, preferably 4 to 8% by weight, of vinyltrimethoxysilane; and 1 to 3% by weight, preferably 1 to 2% by weight, of tetrakis(2-ethylhexyl) orthotitanate; Item 2. The vehicle composition according to item 1, further comprising 1 to 5% by weight, preferably 2 to 3% by weight, of zirconium octylate as a solid content relative to 100% by weight of the solid content of the above components. [8] A two-part composition comprising a first composition and a second composition, The first composition contains at least a polysiloxane compound, the polysiloxane compound being a silicone resin represented by general formula (1), a polysiloxane compound being a silicone resin or polysiloxane compound represented by general formula (2), the polysiloxane compound being a silicone resin represented by general formula (3), or a combination thereof; The second composition contains at least zirconium octylate. Item 8. The vehicle composition according to any one of Items 1 to 7. [9] Item 9. A cured product of the vehicle composition according to any one of items 1 to 8, which is an inorganic thick film having a thickness of 5 to 300 μm, characterized in that it contains carbon element of less than 2000 ppm, which is the detection limit of energy dispersive X-ray analysis using a scanning electron microscope, and shows a peak at 2θ=10±2° in an X-ray diffraction pattern.

[10] A method for forming an inorganic thick film, comprising the steps of: applying the composition for forming an inorganic thick film according to any one of items 1 to 8 onto a substrate to form a coating film; and supplying external energy to the coating film to cure it.

[12] Item 11. The method according to item 10, wherein the external energy is supplied by ultraviolet irradiation or heating at 200° C. or less.

[12] Item 9. A composition for forming an inorganic thick film, comprising the vehicle composition according to any one of items 1 to 8 and a function-imparting solid substance.

[13] Item 13. The composition for forming an inorganic thick film according to item 12, wherein the solid content of the vehicle composition is 20 to 80% and the solid content of the function-imparting solid substance is 80 to 20% based on the entire composition.

[14] Item 14. The composition for forming an inorganic thick film according to item 13, wherein the function-imparting solid material is stainless steel flakes, the solid content of the vehicle composition is 30 to 40%, and the solid content of the function-imparting solid material is 60 to 70%.

[15] Item 14. The composition for forming an inorganic thick film according to item 13, wherein the function-imparting solid substance is a phosphorescent material, the solid content of the vehicle composition is 30 to 40%, and the solid content of the function-imparting solid substance is 60 to 70%.

[16] Item 16. A cured product of the composition for forming an inorganic thick film according to any one of items 12 to 15, the composition for forming an inorganic thick film having a thickness of 5 to 300 μm, characterized in that the composition contains less than 2000 ppm of carbon element, which is the detection limit of energy dispersive X-ray analysis in a scanning electron microscope, and shows a peak at 2θ=10±2° in an X-ray diffraction pattern.

[17] A method for forming an inorganic thick film, comprising: applying the composition for forming an inorganic thick film according to any one of items 12 to 15 onto a substrate to form a coating film; and supplying external energy to the coating film to cure it.

[18] Item 17. The method according to item 16, wherein the external energy is supplied by ultraviolet irradiation or heating at 200° C. or less. Effect of the Invention

[0022] The present invention provides an all-inorganic thick film that has the potential to exhibit a semi-permanent service life, contributing to the Sustainable Development Goals (SDGs). Moreover, this all-inorganic thick film breaks the stereotype that there is no innovation in paint coatings, and brings a breakthrough in the paint field. It not only solves the problem of aging infrastructure, but can also be applied in various fields such as energy conservation measures, carbon neutral measures, antibacterial and antiviral measures, and prevention of radioactive material leakage, thereby bringing about "social benefits." [Brief description of the drawings]

[0023] [Figure 1] Photos of aging infrastructure. [Diagram 2] An example of steel maintenance using Stenshell (registered trademark) manufactured by Toyo Aluminium K.K. [Diagram 3] A simulation was conducted comparing the maintenance costs every six years using conventional resin-based paint that does not contain stainless steel metal powder, and the maintenance costs every 15 years using Stenshell (registered trademark) paint that contains high-end stainless steel flake raw material. [Figure 4] Schematic diagram of the corrosion process using steel as an example. [Diagram 5] 1 is a conceptual diagram of a technical field targeted by the present invention. [Figure 6] Schematic diagram of a three-dimensional network with nano-sized silica as nodes. [Figure 7] 1 is an X-ray diffraction pattern of the all-inorganic thick silica coating 1 according to the present invention. [Figure 8] 1 is an X-ray diffraction pattern of an all-inorganic thick silica coating 2 according to the present invention. [Figure 9] The surfaces of all-inorganic thick silica coating 3 according to the present invention and a silica coating of a comparative example. [Figure 10] Transmittance of all-inorganic thick silica coating 3 and the silica coating of the comparative example. [Figure 11] Comparison of water droplet wettability between stainless steel flake-containing all-inorganic thick film 1 according to the present invention and Stenshell (registered trademark) epoxy resin-based undercoat. [Figure 12]1 is a scanning electron microscope image of a cross section of a stainless steel flake-containing all-inorganic thick film 1' according to the present invention. [Figure 13] Elemental analysis results for the cross section of Figure 12. [Figure 14] Elemental mapping of the cross section of Figure 12. [Figure 15] Photograph showing the fluorescence measurement positions of a sample for measuring phosphorescent brightness. [Figure 16] 1 is a comparison of the afterglow brightness between a phosphorescent material-containing inorganic thick film 3 according to the present invention formed on a PET substrate and a phosphorescent material-containing film of a comparative example (Company SA). [Figure 17] 4 shows the results of an environmental resistance test in a natural environment of the phosphorescent-containing inorganic thick film of the present invention. [Figure 18] 3 is a micrograph of a cross section of a ferrite-containing all-inorganic thick film 3. [Figure 19] Measurement results of the electromagnetic wave blocking ability of ferrite-containing all-inorganic thick film 3 (microstrip line). [Figure 20] Measurement results of the electromagnetic wave blocking ability of ferrite-containing all-inorganic thick film 3 (free space method). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0024] The composition for forming an inorganic thick film according to the present invention is a hybrid composition of an inorganic material of a metal or metal oxide (ceramic) and an organometallic compound, which does not contain an organic binder such as a resin. According to the present invention, it is possible to form an all-inorganic thick film having a thickness of several μm to several mm (e.g., 5 μm to 300 μm, 200 μm to 800 μm, 500 μm to 3 mm, etc.) that is dense and strong on a substrate made of various materials.

[0025] 1. Components of the Vehicle Composition The vehicle composition of the present invention comprises: (A) a polysiloxane compound; (B) Silicon-containing compounds (C)organometallic compound; (D) fused silica; (E) Hardener or UV-curable binder Includes all or part of.

[0026] The (A) polysiloxane compound is added to impart viscosity characteristics to the vehicle composition that enable screen printing. Examples of polysiloxane compounds that can be used in the present invention include silicone resins represented by the general formulas (1), (2), and (3). These silicone resins differ in the number of repeating silicate units (or molecular weight), and therefore differ in hardness when cured by themselves. Depending on the substrate and environment to which the vehicle composition is applied, and taking into consideration the desired viscosity characteristics, crack resistance, and adhesion to the substrate, any one of these may be used alone or in combination. An example of the silicone resin represented by the general formula (1) is the silicone resin SILRES (registered trademark) MK manufactured by Wacker Asahi Kasei Silicone Corporation, which is relatively hard when cured alone. An example of the silicone resin represented by the general formula (2) is polydimethylsilicate (PDMS), whose single cured product is relatively soft. An example of the silicone resin represented by the general formula (3) is liquid silicone resin SILRES (registered trademark) MSE100 manufactured by Wacker Asahi Kasei Silicone Co., Ltd.

[0027] Silicone resins represented by general formula (1) have a relatively large molecular weight, so when cured alone they form a hard film. On the other hand, silicone resins represented by general formula (3) have a relatively small molecular weight, so they are liquid before curing, and after curing they form a microscopically fluid film inside the film structure. Silicone resins represented by general formula (2) are somewhere in between, forming a soft film. When combining multiple silicone resins to control the viscosity characteristics, it is preferable to heat them to 60 to 100°C, for example 80°C, and cause dehydration condensation by silanol reaction. Therefore, for example, when a silicone resin represented by general formula (1) and a silicone resin represented by general formula (2) are cured by dehydration condensation, microscopically hard and soft parts coexist inside the film structure, and while the film as a whole is robust, there are locally soft parts (sea-island structure). This makes it possible to prevent structural destruction, i.e., crack generation, caused by the difference in thermal expansion coefficient between the substrate and the film, even if there is a temperature change. In fact, there are phenomena that cannot be explained by the sea-island structure alone, so the inventors conducted further research. As a result, it was confirmed that a homogeneous film with reduced cracking was formed when a silane compound that links in a straight chain under acidic conditions was used as a trigger to start the silanol reaction. In this case, if the reaction is carried out under alkaline conditions, three-dimensional cross-linking occurs and the film becomes lumpy. Hybrid polysiloxane compounds formed by linking multiple silicone resins in a linear chain have unreacted methyl groups at the ends and side chains, which makes them fluid at a microscopic level. An appropriate amount of a hardener such as zirconium octylate is added to this hybrid polysiloxane compound to react with the unreacted groups to create a three-dimensional structure. This procedure results in a three-dimensional structure with many uncrosslinked areas, i.e., broken meshwork. In other words, it was found that the weak areas in the network (crushable structure) can absorb external strain and prevent cracks from occurring. In the present invention, the formation of such sea-island structures and crushable structures is controlled depending on the application and usage environment of the inorganic thick film.

[0028] (B) The silicon-containing compound acts as a node when crosslinking the polysiloxane compound to form a three-dimensional network. Silicon-containing compounds that can be used in the present invention include silane compounds such as tetraalkylorthosilicate (also called "tetraalkoxysilane"; TEOS), silica, a mixture of TEOS and silica, vinyltrimethylsilane, which is known as a silane coupling agent, or a combination thereof. Silane compounds such as TEOS can be hydrolyzed to nano-sized silica in the presence of moisture. Nano-sized silica can also be used directly. Nano-sized silica can also be produced from silane compounds such as TEOS using the sol-gel method.

[0029] Examples of silane compounds that can be used in the present invention include Wacker® SILICATE TES 28 and Wacker® SILICATE TES 40 WN. Wacker® SILICATE TES 28 is a monomeric ethyl silicate that is a low-viscosity, colorless liquid containing approximately 28% by weight of SiO2 through hydrolysis. Si-O- formation through hydrolysis is rapid. Wacker® SILICATE TES 40 WN is an ethyl silicate polymer, a low-viscosity liquid that produces approximately 41% by weight of SiO2 upon complete hydrolysis. It is slow to convert Si-O- to SiO2 by hydrolysis, and is easily bonded to polydialkylsilicates such as PDMS.

[0030] In the present invention, the polysiloxane compound (A) can be mixed with a portion of the silicon-containing compound (B) to be used as a mixture of the two components, or this mixture can be further reacted to use as a reactant. The reaction product of (A) a polysiloxane compound and (B) a silicon-containing compound can be obtained, for example, by mixing PDMS with a silane compound such as TEOS and heating it together with a catalyst. For example, there is a product such as "EL0039G", a silicone resin compound manufactured by Gootec Co., Ltd. (sales agent: Juke Co., Ltd.). The reaction product of such (A) a polysiloxane compound and (B) a silicon-containing compound (for example, the silicone resin formulation described above) forms a three-dimensional network with nano-sized silica as nodes (Figure 6).

[0031] The organometallic compound (C) is added to facilitate the progress of the dehydration condensation reaction between the polysilanol compounds. Examples of organometallic compounds that can be used in the present invention include Orgatix TC-750 (titanium diisopropoxybis(ethylacetoacetate) [Ti(Oi-C3H7)2(C6H9O3)2]) manufactured by Matsumoto Fine Chemical Co., Ltd., and tetrakis(2-ethylhexyl) orthotitanate.

[0032] (D) Fused silica is an agglomerate with a high specific surface area and a chain structure of spherical particles. Silanol groups exist on the surface of the particles and are involved in the formation of a network with polysilanol compounds. An example of the fused silica that can be used in the present invention is AEROSIL (registered trademark) R850 manufactured by Nippon Aerosil Co., Ltd.

[0033] (E) The hardener or UV-curable binder accelerates the hydrolysis reaction of polysilanol compounds, silane compounds, and the like. C is a compound known as a curing agent or UV curable binder that can be used in the present invention. 6~25 Examples of the metal salts include carboxylic acids such as hexyl acid, octyl acid, 2-ethylhexanoic acid, lauric acid, myristic acid, palmitic acid, stearic acid, ricinoleic acid, and behenic acid with Co, Mn, Zn, Sn, Zr, Fe, Ni, Ca, K, and Li, and preferably Zr, Sn, and Zn. More preferred is zirconium octyl acid, and examples thereof include Nikka Octix (registered trademark) zirconium [zirconium octyl acid] manufactured by Nippon Kagaku Sangyo Co., Ltd. On the other hand, when Ti is used as the metal, the reaction is too fast in the present invention, making it difficult to use.

[0034] (F) The catalyst is added to facilitate the progress of hydrolysis of the polysilanol compound. When the silanol groups of the polysilanol compound or silane compound are hydrolyzed and dehydration condensation occurs, water may be generated, causing foaming. In order to substantially suppress the generation of foaming while allowing the hydrolysis to proceed, a very small amount of water and acid is added in comparison with the amount of the polysilanol compound. As the acid, organic acids such as formic acid, acetic acid, citric acid, malic acid, lactic acid, succinic acid, tartaric acid, fumaric acid, etc., and inorganic acids such as hydrochloric acid, nitric acid, sulfuric acid, etc. can be used. Organic acids are preferable to inorganic acids because they cause a milder reaction, and acetic acid is more preferable.

[0035] (G) Solvent This is an optional component for adjusting the viscosity of the paint. Solvents that can be used in the present invention include isopropyl alcohol (IPA), 2,2,4-trimethylpentane-1,3-diol monoisobutyrate (Texanol), butanol, and butyl carbitol acetate (BCA).

[0036] 2. Functionalized solid materials The vehicle composition of the present invention can form a useful all-inorganic thick film by using the silanol structure as it is, but various functional solid substances can be added depending on the technical field to which it is applied. Examples of functionalized solid substances that can be used in the present invention include stainless steel metal powders (e.g., stainless steel flakes), phosphorescent agents (e.g., strontium aluminate Sr4Al activated with dysprosium or europium), and the like. 14 O 25 :Eu,Dy) or fluorescent agents, photocatalysts (e.g., TiO2, WO3), antibacterial agents (e.g., chlorhexidine gluconate), T-chromics (e.g., VO2), radiation shielding agents (e.g., Ba, Ti), insulators (e.g., Al2O3, C-AIN, Low-K), visible / UV light reflectors (e.g., Zr), etc.

[0037] 3. Membrane An inorganic thick film prepared using the vehicle composition of the present invention or a composition for forming an inorganic thick film containing a function-imparting solid substance does not contain C at a concentration exceeding 1500 to 2000 ppm, which is the analytical detection limit of SEM-EDS, and exhibits a peak at 2θ=10±2° with C Kα radiation in X-ray diffraction analysis. This peak has not been detected in conventional polysiloxane compounds or silane compounds.

[0038] 4.Base material Substrates to which the inorganic thick film of the present invention can be applied include a wide variety of materials, such as metals, ceramics, glass, plastics, concrete, wood, woven fabrics, nonwoven fabrics, and paper.

[0039] 5. Film formation process The film formation of the present invention includes the steps of applying a vehicle composition to a substrate and curing the coating by supplying external energy to the coating. The external energy used in the present invention is ultraviolet irradiation or heating at 200°C or less, and there is no need to use expensive equipment or processes that are limited in size or location of the target. The source of ultraviolet light includes natural light, and heating at 200°C or less broadly includes leaving it at room temperature. The treatment process depends on the external energy used, the target, and the usage environment, but may be 10 to 60 minutes, 3 hours, 5 hours, 10 hours, half a day, 1 day, etc. A preliminary drying step may be included before the curing step. When the vehicle composition contains a solvent for adjusting the viscosity, the solvent is removed at a temperature between room temperature and about 100° C. When the temperature is raised in the curing step, the solvent may be removed for a period of time that is long enough to prevent the internal solvent from expanding suddenly and causing structural destruction, and is usually 5 to 30 minutes, half a day, one day, etc.

[0040] The all-inorganic thick film technology of the present invention is a further development of optical MOD, and has been named Advanced MOD (registered trademark). EXAMPLES

[0041] A. Vehicle Composition [Example 1] (1) Preparation of vehicle composition for 4G room temperature curing material As polysiloxane, 12.3 wt% SILRES (registered trademark) MK (Asahi Kasei Silicone Corporation silicone resin: solid content 100 wt%), 4.7 wt% PDMS and 74.9 wt% SILRES (registered trademark) MSE100 (Asahi Kasei Silicone Corporation silicone resin: solid content 70 wt%); as organometallic compound, 6.9 wt% Orgatics TC-750 (registered trademark) (Matsumoto Fine Chemical Co., Ltd. titanium diisopropoxy bis (ethyl acetoacetate): solid content 10.45 wt%); as fused silica, 1.2 wt% AEROSIL (registered trademark) R850 (Nippon Aerosil Co., Ltd. fused silica: solid content 100 wt%) were stirred at room temperature (about 25 ° C) for 20 minutes with a tornado mixer (600 rpm) to prepare a vehicle composition 1' having a viscosity suitable for screen printing.

[0042] [Table 1]

[0043] (2) Formation of an all-inorganic thick silica coating Just before use, 3.0% by weight of zirconium octylate was added as a curing agent to 100% by weight of vehicle composition 1' to obtain vehicle composition 1 for 4G room temperature curing material. Vehicle composition 1 for 4G room temperature curing material was applied onto a quartz glass substrate, and the resulting coating was left overnight at room temperature (about 25°C) to form an all-inorganic thick film silica coat 1 with a thickness of about 150 μm. The adhesion to the substrate was good. A vehicle composition 1 for 4G room temperature curing material was applied onto a PET sheet and left overnight at room temperature (about 25° C.) to form an all-inorganic thick silica coat 1′ having a thickness of about 150 μm.

[0044] (3) X-ray diffraction analysis By X-ray diffraction analysis, an Au sputtered film of about 20 nm thickness was formed on the all-inorganic thick-film silica coating 1 formed on a quartz glass substrate, and the X-ray diffraction pattern was measured. The measurement results are shown in Table 2 and Figure 7. In Figure 7, the X-ray diffraction pattern of the all-inorganic thick-film silica coating 1 is shown by subtracting the X-ray diffraction pattern of the quartz glass alone from the X-ray diffraction pattern of the quartz glass on which the all-inorganic thick-film silica coating 1 is formed.

[0045] [Table 2]

[0046] As shown in Table 2, the composition analysis showed that most of the composition was Si-O. A trace amount of Ti was detected, which was derived from the orgatics. Al was derived from the sample holder, and Au was derived from the Au sputtered film. On the other hand, no C was detected at all, which indicates that the all-inorganic thick silica coating 1 does not contain any organic matter.

[0047] As can be seen from Figure 7, a halo pattern (Non-Patent Document 4) typical of amorphous glass was observed around 2θ = 20°. In addition, a high intensity diffraction peak was observed at 2θ = 10.52°. SiO2 showing such a diffraction pattern is not known. Pyrophyllite (Al2Si4O 10 (OH)2) is known. It is also known that pyrophyllite shows peaks at 2θ=9.6°, 19.3°, and 29.1° in the X-ray diffraction pattern, with the peaks at 2θ=9.6° and 29.1° having similar peak intensities, and the peak at 2θ=19.3° having half the peak intensity of the two. In addition, Al comes from the sample holder and is less than 1% of the amount of Si present, so it is impossible for a single peak to show an intensity greater than the halo pattern of amorphous SiO2. Therefore, it was confirmed that the all-inorganic thick silica coat 1 according to the present invention has a structure exhibiting crystal characteristics different from those of conventional coatings.

[0048] [Example 2] (1) Preparation of vehicle composition for 3G thermosetting materials As polysiloxanes, 74.0% by weight of SILRES (registered trademark) MK (Asahi Kasei Wacker Silicone Co., Ltd. silicone resin: solid content 100% by weight) and 14.1% by weight of PDMS; as organometallic compounds, 9.2% by weight of TES reagent Si41 (Wacker (registered trademark) SILICATE TES 40 WN) and 1.8% by weight of TEOS reagent Si28 (Wacker (registered trademark) SILICATE TES 28); and as fused silica, 0.9% by weight of AEROSIL (registered trademark) R850 (Nihon Aerosil Co., Ltd. fumed silica) were mixed to obtain a mixture, to which 0.5% by weight of water and 0.5% by weight of acetic acid were further added, and the mixture was stirred at 80 ° C. with a tornado mixer (600 rpm) for 65 minutes to prepare a vehicle composition 2' for 3G thermosetting materials having a viscosity suitable for screen printing.

[0049] [Table 3]

[0050] (2) Formation of an all-inorganic thick silica coating Just before use, 2.0% by weight of zirconium octylate was added as a curing agent to 100% by weight of vehicle composition 2' to obtain 3G thermosetting material vehicle composition 2. 3G thermosetting material vehicle composition 2 was applied onto a quartz glass substrate, and the resulting coating was heated at 180°C for 1.5 hours (1 to 2 hours) to form an all-inorganic thick film silica coat 2 having a thickness of about 150 μm.

[0051] (3) X-ray diffraction analysis By X-ray diffraction analysis, an Au sputtered film of about 20 nm thickness was formed on the all-inorganic thick silica coating 2 formed on a quartz glass substrate, and the X-ray diffraction pattern was measured. The measurement results are shown in Figure 8. In Figure 8, the X-ray diffraction pattern of the all-inorganic thick silica coating 2 is shown by subtracting the X-ray diffraction pattern of the quartz glass alone from the X-ray diffraction pattern of the quartz glass on which the all-inorganic thick silica coating 2 is formed.

[0052] As with All-inorganic Thick Silica Coat 1, the composition analysis showed that most of the composition was Si-O. A trace amount of Zr was detected, which was derived from zirconium octylate. The Al was derived from the sample holder, and the Au was derived from the Au sputtered film. On the other hand, no C was detected at all, which indicates that the all-inorganic thick silica coat 2 does not contain any organic matter.

[0053] As can be seen from Figure 8, a halo pattern typical of amorphous glass was observed around 2θ = 20°. In addition, a high intensity diffraction peak was observed at 2θ = 10.52°. No SiO2 was known to show such a diffraction pattern. Therefore, it was confirmed that the all-inorganic thick silica coat 2 according to the present invention has a structure exhibiting crystal characteristics different from those of conventional coatings.

[0054] [Example 3] (1) Preparation of vehicle composition for phosphorescent material 30.0 wt% SILRES (registered trademark) MK (silicone resin from Wacker Asahi Kasei Silicones Co., Ltd.: solid content 100 wt%) as polysiloxane; 10.0 wt% vinyl methoxy silane as organometallic compound (silane coupling agent); and 60.0 wt% zirconium octylate as UV curing binder were mixed and stirred at 2000 rpm for 3 minutes in a planetary mixer (THINKY Mixer manufactured by THINKY Corporation) to prepare vehicle composition 3 for phosphorescent materials having a viscosity suitable for screen printing.

[0055] [Table 4]

[0056] (2) Formation of an all-inorganic thick silica coating Three sheets of Scott tape with a thickness of about 55 μm were laminated (about 165 μm) on a 0.8 mm thick white glass substrate to create an area of ​​about 4 cm × about 4 cm square. An appropriate amount of vehicle composition 3 prepared immediately before use was placed on this area, and a coating film of uniform thickness was formed by hand drawing with an applicator for a grind gauge by the doctor blade method. The white glass substrate was temporarily dried at 90°C for 10 minutes in a hot air drying oven, and then heated and cured at 130°C for 60 minutes to form an all-inorganic thick film silica coat 3 with a thickness of about 130 μm. For comparison, a thin film coating was formed using a photo-MOD composition in which vinyltrimethoxysilane was added as a silane coupling agent to zirconium octylate. This photo-MOD composition was in liquid form.

[0057] (3) Properties of all-inorganic thick silica coating The all-inorganic thick silica coat 3 is a uniform, transparent film with no cracks (FIG. 9a), whereas the silica coat of the comparative example is a transparent film with cracks (FIG. 9b). Next, the transmittance of the all-inorganic thick-film silica coating 3 formed on a white glass plate and the silica coating of the comparative example was measured using a spectrophotometer (Fig. 10). For the all-inorganic thick-film silica coating 3, the transmittance was 90-92% in the visible light range (400nm<) and 83-85% in the ultraviolet range (350-400nm), while for the silica coating of the comparative example, the transmittance was approximately 85% in the visible light range (400nm<) and 80-83% in the ultraviolet range (350-400nm). It has been confirmed that zirconium octylate turns yellow when cured at temperatures below 500°C (Table 5). However, because All Inorganic Thick Silica Coat 3 contains SILRES MK, a polysiloxane, the concentration of zirconium octylate within the film is reduced, and yellowing was not an issue.

[0058] [Table 5]

[0059] [Example 4] (1) Preparation of vehicle composition for antibacterial agent A vehicle composition 4 for an antibacterial agent having a viscosity suitable for screen printing was prepared by mixing 46.5% by weight of SILRES (registered trademark) MK (silicone resin from Wacker Asahi Kasei Silicones Co., Ltd.: solid content 100% by weight) as a polysiloxane; 7% by weight of vinylmethoxysilane (silane coupling agent) as an organometallic compound; and zirconium octylate as a curing agent.

[0060] [Table 6]

[0061] [Example 5] (1) Preparation of vehicle composition for antibacterial agent 98.0% by weight of PDMS as polysiloxane and tetrakis(2-ethylhexyl) orthotitanate as organometallic compound were stirred at 80° C. for 45 minutes in a tornado mixer (600 rpm) to prepare vehicle composition 5′ for an antibacterial agent having a viscosity suitable for screen printing. 3.0% by weight of zirconium octylate as a curing agent was added to 100% by weight of vehicle composition 2′ to prepare vehicle composition 5.

[0062] [Table 7]

[0063] [Example 6] (1) Preparation of Thermochromic Vehicle Composition 93.4 wt% PDMS as polysiloxane, 1.7 wt% tetrakis(2-ethylhexyl) orthotitanate as organometallic compound, and 4.9 wt% vinylmethoxysilane (silane coupling agent) were stirred for 45 minutes at 80° C. with a tornado mixer (600 rpm) to prepare a vehicle composition 7′ for thermochromic PDMS modification. 3.0 wt% zirconium octylate as a curing agent was added to 100 wt% vehicle composition 6′ for thermochromic PDMS modification to obtain a vehicle composition 6 for thermochromic modification having a viscosity suitable for screen printing.

[0064] [Table 8]

[0065] [Example 7] (1) Preparation of a composition for forming an all-inorganic thick film containing stainless steel flakes 46.1 g of vehicle composition 1' (solid content 32.8 g) and 53.9 g of Stainless Shell 70 (manufactured by Toyo Aluminum Co., Ltd., solid content 53.9 g) as stainless steel flakes were stirred at 80°C for 45 minutes using a tornado mixer (600 rpm) to obtain an all-inorganic thick film forming composition 1' containing stainless steel flakes (solid content, vehicle composition:stainless steel flakes = 38:62).

[0066] (2) Formation of stainless steel flake film Just before use, 1.5% by weight of zirconium octylate was added to 100% by weight of the all-inorganic thick film-forming composition 1' to obtain the all-inorganic thick film-forming composition 1. The all-inorganic thick film-forming composition 1 was applied onto a 0.6 mm thick stainless steel substrate and left overnight at room temperature (about 25°C) to form a stainless steel flake-containing all-inorganic thick film 1a having a thickness of about 40 µm. The inorganic thick film-forming composition 1 was applied onto a PET sheet and left to stand overnight at room temperature (about 25° C.) to form a stainless steel flake-containing inorganic thick film 1b having a thickness of about 40 μm.

[0067] (3) Properties of inorganic thick films containing stainless steel flakes The wettability of the stainless steel flake-containing inorganic thick film 1 formed on a stainless steel substrate was compared with that of a coating formed in the same manner using Stenshell (registered trademark) epoxy resin-based intermediate coating (manufactured by Toyo Aluminum K.K.) (FIG. 11). The stainless steel flake-containing inorganic thick film 1 is shown on the right, and the Stenshell (registered trademark) epoxy resin-based intermediate coating film is shown on the left. It can be seen that the water repellency of water droplets dropped onto the stainless steel flake-containing inorganic thick film 1 is higher than that of the Stenshell (registered trademark) epoxy resin-based intermediate coating film. This indicates that the surface of the stainless steel flake-containing inorganic thick film 1 is hydrophobic, which is thought to be due to the absence of resin components.

[0068] (4) Cross-sectional structure of stainless steel flake membrane The stainless steel flake-containing inorganic thick film 1' formed on the PET sheet was cut, and an electron micrograph (Figure 12) and elemental analysis (Figures 13 and 14) of the film cross section were taken using a scanning electron microscope equipped with an energy dispersive X-ray analyzer. Electron microscope images show that stainless steel flakes are densely layered on the PET substrate (Figure 12). Furthermore, elemental analysis revealed that there were a lot of Si and Fe in the cross section, as well as the presence of C and O (Figure 13). Elemental mapping of the cross section was performed. Figure 14 shows a cross section photograph (first row from the top left), mapping of C Kα radiation (second row from the top left), Si Kα radiation (third row from the top left), and Fe Kα radiation (fourth row from the top left). The combined mapping, including the mapping of O Kα radiation (not shown), is shown on the right side of Figure 14. According to the composite mapping, Fe, Si and O were present only in the stainless steel flake laminates, and no C was found in the stainless steel flake laminates, but only in the PET substrate. The detection limit of energy dispersive X-ray analysis in a scanning electron microscope is 1500-2000 ppm, so the amount of carbon in the stainless steel flake laminates was less than 2000 ppm, confirming that there was virtually no organic matter present, i.e., that it was "all inorganic." This confirmed that by using the composition for forming an inorganic thick film of the present invention, a thick film made of substantially only inorganic materials (all-inorganic thick film) can be formed on a PET substrate having low heat resistance.

[0069] [Example 8] (1) Preparation of composition for forming inorganic thick film containing phosphorescent material 34 g of vehicle composition 3 (solid content 31.3 g) prepared immediately before use and 66 g of phosphorescent material LumiNova GLL300M (Nemoto Special Chemicals: strontium aluminate Sr4Al activated with dysprosium and europium) were added. 14 O 25 The mixture (solid content: 66 g) was stirred at room temperature (about 25° C.) for 20 minutes with a tornado mixer (600 rpm) to obtain an all-inorganic thick film-forming composition 2 containing a phosphorescent material (solid content: vehicle composition: phosphorescent material=32:68).

[0070] (2) Formation of phosphorescent film Three sheets of Scott tape with a thickness of about 55 μm were laminated (about 165 μm) on a PET substrate to create an area of ​​about 10 cm × about 9 cm square. An appropriate amount of all-inorganic thick film forming composition 2 prepared immediately before use was placed in this area, and a coating film of uniform thickness was formed by hand drawing with an applicator for a grind gauge using the doctor blade method. This coating film was irradiated with 385 nm UV light to form an all-inorganic thick film 2 containing a phosphorescent material. For comparison, a luminescent-containing resin cured film was formed in the same manner as above using a conventional luminescent paint (manufactured by SA) containing an acrylic resin binder.

[0071] (3) Fluorescence properties of phosphorescent film The phosphorescence characteristics were confirmed for the phosphorescent material-containing all-inorganic thick film 2 formed on a PET substrate and the phosphorescent material-containing film of the comparative example (Company SA). The measurement positions of the phosphorescence measurement samples are shown in Figure 15 (right: all-inorganic thick film 2 of the present invention (Advanced MOD (registered trademark)), left: conventional phosphorescent material-containing resin cured film). These films were (a) irradiated with a Xe lamp at 1000 lx for 5 min and (b) 65The afterglow luminance was measured under two excitation conditions of 200 lx fluorescent lamp irradiation for 20 minutes. The results are shown in Table 9 and Figure 16.

[0072] [Table 9]

[0073] Table 9 shows the results of measuring the afterglow luminance of each film after a certain time from excitation by light irradiation, and the ratio of the luminance of the all-inorganic thick film 2 to the luminance of the conventional film. As described above, the phosphorescent-containing inorganic thick film 2 according to the present invention not only has a higher luminance immediately after excitation, but also has improved afterglow luminance compared to the conventional phosphorescent-containing resin cured film.

[0074] (4)Environmental resistance Next, an example of an environmental resistance test in a natural environment is shown in Figure 17. Although it is not a precise durability test, the following images are shown after 10 months of attaching a label of the phosphorescent-containing inorganic thick film of the present invention to the mudguard of the rear wheel of a bicycle: (a) in a dimly lit room illuminated by the room light, (b) in the same room when moved to a location not directly illuminated by the room light, and (c) illuminated by the headlights of a car. It is known that phosphorescent materials deteriorate quickly when they come into contact with moisture. The cured film of phosphorescent resin obtained from a composition formed from a polymer paste using a conventional acrylic resin is not suitable for outdoor use exposed to rain and wind, and the surface must be protected with a film. On the other hand, it has been confirmed that the phosphorescent-containing inorganic thick film of the present invention maintains its initial brightness even though it is not protected with a film.

[0075] (5) Discussion Based on elemental mapping of the stainless steel flake film and comparison with a film obtained from a phosphorescent paint containing an acrylic resin, it is assumed that the phosphorescent particles are dispersed within the structure of the siloxane compound. Therefore, it is believed that the environmental resistance is significantly improved because the phosphorescent particles are covered with the siloxane compound. It is also known that siloxane compound has higher light transmittance than acrylic resin cured material.Therefore, in conventional luminescent material-containing resin cured film, the light from the surface cannot reach the shallow area of ​​the film, and cannot fully excite the luminescent material present in the deep part, but the light from the surface of the luminescent material-containing inorganic thick film of the present invention can reach the deep part, effectively excite the luminescent material present in the film, and also emit the emitted light to the outside.

[0076] [Example 9] (1) Preparation of a composition for forming a ferrite-containing inorganic thick film 34 g of vehicle composition 2 for 3G heat curing agent (solid content 31.3 g) and 61.5 g of ferrite material MZ20 particle size 22.1 (Mn-Zn ferrite) 275 g INN (Powder Tech) (solid content 61.5 g) prepared just before use were stirred with a tornado mixer (600 rpm) at room temperature (about 25°C) for 20 minutes to obtain an all-inorganic film-forming composition 3 containing the ferrite material (solid content: vehicle composition 2 for 3G heat curing agent:ferrite material = 38:62).

[0077] (2) Formation of ferrite film On a PET substrate, the all-inorganic thick film forming composition 3 prepared immediately before use was applied in an area of ​​about 15 cm x 15 cm square, with 100% by weight of diisopropoxybis(ethylacetoacetate)titanium (TC-750 Ti Acetoana) added as a curing agent at 0.40% by weight. A coating film of uniform thickness was formed by screen printing. Three levels of coating thickness were prepared so that the final thickness was about 100 μm / 150 μm / 210 μm. This coating was heated at 130° C. to form a ferrite-containing all-inorganic thick film 3 .

[0078] (3) Electromagnetic wave blocking properties of ferrite films The electromagnetic wave blocking properties of the ferrite-containing all-inorganic thick film 3 formed on the PET substrate were confirmed. FIG. 18 shows micrographs of the cross sections of all-inorganic thick films 3 of three thickness levels of approximately 100 μm / 150 μm / 210 μm, which were prepared as samples (the present invention (Advanced MOD (registered trademark))) for measuring the electromagnetic wave blocking properties. The PET substrate side of the obtained thick film is smooth, but the upper surface is uneven. Therefore, the smooth side was placed on the front side and the electromagnetic wave blocking ability was measured using a microstrip line (0.1-6 GHz / 3-14 GHz) and the free space method (12.4-45 GHz). In the free space method, the absorption rate (%) and the complex reflection coefficient S, which is a component of the scattering matrix S parameter, were measured. 11 It was evaluated as follows. The measurement results are shown in FIG. 19 and FIG.

[0079] (4) Discussion Although there was thickness dependence, the electromagnetic wave blocking ability of the 210 μm thick ferrite-containing inorganic thick film was measured and good results were obtained using both the microstrip line (0.1 to 6 GHz / 3 to 14 GHz) and the free space method (12.4 to 45 GHz).

[0080] [Example 10] (1) Preparation of a composition for forming a tungsten-containing inorganic thick film Two types of compositions were prepared: room temperature curing type tungsten-containing inorganic film-forming composition 4a using 4G room temperature curing material vehicle composition 1, and thermosetting type tungsten-containing inorganic film-forming composition 4b using 3G thermosetting material vehicle composition 2. In both compositions, stainless steel flake powder, aluminum oxide powder, and synthetic mica powder were added as solids in addition to tungsten material to prevent cracks when applied thickly. 20 g of 4G inorganic hardener vehicle composition 1 prepared immediately before use, 72.4 g of tungsten material (Nippon Shinkinzoku W3:W4 25:75 blend ratio), 6.5 g of stainless steel flake powder (Toyo Aluminum Stainless Shell Paste 70), and 1.1 g of aluminum oxide powder (low soda alumina AL-47-H) were stirred at room temperature (about 25°C) for 20 minutes with a tornado mixer (600 rpm) to obtain a tungsten-containing 4G room temperature curing type all-inorganic film-forming composition 4a (weight ratio of 4G room temperature curing vehicle composition 1: tungsten material / stainless steel flake powder / aluminum oxide powder = 20:80). 19.5 g of 3G thermosetting material vehicle composition 2 prepared immediately before use, 80.0 g of tungsten material (Nippon Shinkinzoku W3:W4 25:75 blend ratio), and 0.5 g of synthetic mica (Topy Industries PDM-800 / 1000) were stirred for 20 minutes at room temperature (about 25°C) with a tornado mixer (600 rpm) to obtain a 3G thermosetting type all-inorganic film-forming composition 4b containing tungsten material (weight ratio of 3G thermosetting material vehicle composition 2: tungsten material / stainless steel flake powder / aluminum oxide powder = 19.5:80.5).

[0081] (2) Formation of tungsten film The all-inorganic film-forming composition 4a is taken as 100% by weight, and 0.4 to 0.6% by weight of diisopropoxybis(ethylacetoacetate)titanium (TC-750 Ti Acetoana) is added later as a curing agent. The all-inorganic film-forming composition 4b is taken as 100% by weight, and 2.0% of zirconium octylate is added later as a curing agent. Each composition was screen-printed on a steel plate substrate in an area of ​​about 20 cm x about 20 cm to form a coating film of uniform thickness. Samples were prepared with a coating thickness of about 65 μm in the final film thickness. The coating of the room temperature curing type all-inorganic film forming composition 4a was cured at room temperature to form a tungsten-containing inorganic film 4a, and the heat curing type all-inorganic film forming composition 4b was cured by heating at 180°C to form a tungsten-containing inorganic film 4b.

[0082] (3) X-ray blocking properties of tungsten film Since X-rays are not blocked by steel sheets, samples for measuring X-ray shielding ability were prepared by stacking 10 steel sheet substrates (total inorganic film thickness: 650 μm) and 12 steel sheet substrates (total inorganic film thickness: 780 μm) on which tungsten-containing inorganic films were formed. At the Tokyo Metropolitan Industrial Technology Research Institute, the X-ray shielding properties (X-ray dose rate) of 100kV and 400kV narrow beams were measured according to the method specified in JIS Z 4501 "Testing method for lead equivalent of X-ray protective equipment." The shielding rate was calculated by subtracting the measured transmittance (%) from 100%. The results of these measurements are shown in Table 10.

[0083] [Table 10]

[0084] (4) Discussion Although it depends on the thickness, the X-ray shielding ability at an X-ray intensity of 100 kV was equal to or better than that of radiation (X-ray) protection aprons made of lead-containing materials used in X-ray inspections. [Industrial Applicability]

[0085] According to the present invention, a composition for forming an "all-inorganic thick film" consisting of only inorganic materials such as metals or metal oxides (ceramics) and having a thickness of several μm to several mm, that is, an "all-inorganic thick film," on various materials can be obtained. If such an "all-inorganic thick film" is used to repair or prevent the deterioration of infrastructure, which is a public good, or to be applied to various other purposes, it is possible to achieve the Sustainable Development Goals, thereby bringing about social benefits. [Explanation of symbols]

[0086] 1 Nanosilica Node 2 Polysilanol Net

Claims

1. The solid content of each component is as follows: (A) 15 to 70% by weight of a polysiloxane compound having the general formula (1): 【Chemistry 1】 (wherein R 1 and R 2 are each independently a hydrogen atom, a C 1-3 alkyl group, or a C 1-3 alkoxy group; m1 and n1 are each independently an integer of 1 to 100, where m1+n1=10 to 100; and both ends of the main chain may independently be bonded to a hydrogen atom or a C 1-3 alkyl group); 2 to 8% by weight of a polysiloxane compound having the general formula (2): 【Chemistry 2】 (wherein p is an integer of 250 to 400, and both ends of the main chain may independently be bonded to a hydrogen atom or a C 1-3 alkyl group); and 20 to 85% by weight of a polysiloxane compound having the general formula (3): 【Chemistry 3】 (In the formula, R 3 and R 4 Each independently represents a hydrogen atom, C 1~3 Alkyl group or C 1~3 m2 and n2 are each independently an integer of 1 to 10, and m2+n2=1 to 10. Both ends of the main chain are independently a hydrogen atom or a C 1~3 An alkyl group may be bonded to the silicone resin. A combination of: (C) 0.5 to 3 weight percent titanium diisopropoxybis(ethylacetoacetate); and (D) 0.5 to 3 weight percent fused silica and further comprising, as a solid content, based on 100% by weight of the solid content of the components (A), (C) and (D), (E) 1 to 5% by weight of zirconium octylate A vehicle composition comprising:

2. A two-part composition comprising: The first composition contains at least (A) a polysiloxane compound, The second composition contains at least zirconium octylate as a curing agent (E). The vehicle composition of claim 1 .

3. The solid content of each component is as follows: (A) 45 to 85% by weight of a polysiloxane compound having the general formula (1): 【Chemistry 1】 (wherein R 1 and R 2 are each independently a hydrogen atom, a C 1-3 alkyl group, or a C 1-3 alkoxy group; m1 and n1 are each independently an integer of 1 to 100, where m1+n1=10 to 100; and both ends of the main chain may independently be bonded to a hydrogen atom or a C 1-3 alkyl group); and 7 to 24% by weight of a polysiloxane compound having the general formula (2): 【Chemistry 2】 (wherein p is an integer of 250 to 400, and both ends of the main chain may independently be bonded to a hydrogen atom or a C 1-3 alkyl group). A combination of: (B) 2-7% by weight of a TES reagent Si41 and 0.2-1.5% by weight of a TEOS reagent Si28, wherein the TES reagent Si41 is an ethylsilicate polymer and the TEOS reagent Si28 is a monomeric form of ethylsilicate; and (D) 0.5 to 3 weight percent fused silica and further comprising, relative to 100% by weight of the solid content of the components (A), (B) and (D), 0.3 to 3% by weight of water and 0.3 to 3% by weight of acetic acid are added, and further, as solids, (E) 1 to 5% by weight of zirconium octylate A vehicle composition comprising:

4. A two-part composition comprising: The first composition contains at least (A) a polysiloxane compound, The second composition contains at least zirconium octylate as a curing agent (E). The vehicle composition of claim 3.

5. A cured product of the vehicle composition according to any one of claims 1 to 4, comprising carbon element of less than 2000 ppm, which is the detection limit of energy dispersive X-ray analysis using a scanning electron microscope, and exhibiting a peak at 2θ = 10 ± 2° in an X-ray diffraction pattern, and having a film thickness of 5 to 300 μm.

6. A method for forming an inorganic thick film, comprising the steps of: applying the vehicle composition according to any one of claims 1 to 4 onto a substrate to form a coating film; and supplying external energy to the coating film to cure it.

7. The method according to claim 6 , wherein the external energy is supplied by ultraviolet irradiation or heating at 200° C. or less.

8. 5. A composition for forming an inorganic thick film, comprising the vehicle composition according to claim 1 and a function-imparting solid substance.

9. 9. The inorganic thick film forming composition according to claim 8, wherein the solid content of said vehicle composition is 20 to 80% and the solid content of said function-imparting solid substance is 80 to 20% based on the entire composition.

10. 10. The composition for forming an inorganic thick film according to claim 9, wherein the function-imparting solid material is stainless steel flakes, the solid content of the vehicle composition is 30-40%, and the solid content of the function-imparting solid material is 60-70%.

11. The composition for forming an inorganic thick film according to claim 9, wherein the function-imparting solid material is a phosphorescent material, the solid content of the vehicle composition is 30-40%, and the solid content of the function-imparting solid material is 60-70%.

12. A cured body of the composition for forming an inorganic thick film according to claim 8, which contains carbon element of less than 2000 ppm, which is the detection limit of energy dispersive X-ray analysis in a scanning electron microscope, and shows a peak at 2θ=10±2° in an X-ray diffraction pattern, and has a film thickness of 5 to 300 μm.

13. A method for forming an inorganic thick film, comprising the steps of: applying the composition for forming an inorganic thick film according to claim 8 onto a substrate to form a coating film; and supplying external energy to the coating film to cure it.

14. The method according to claim 13 , wherein the external energy is supplied by ultraviolet irradiation or heating at 200° C. or less.

Citation Information

Patent Citations

  • JP1974020739A

  • Releasable film composition for forming

    JP1983219270A

  • Polyorganosiloxane composition

    JP1984012964A

  • Prevention of freezing on base material

    JP1987127381A

  • Heat-resistant coating composition

    JP1988270768A